The Wordsworth Dictionary of Mythology - Comte, Fernand (Wordsworth Editions Ltd, 1994)
This encyclopedic guide includes gods from ancient civilizations such as Aphrodite, Quetzalcoatl and Vishnu and legendary heroes from Achilles to Visvamitra,in an A-Z of exotic stories.
Keywords: Mythology-Dictionaries-Non fiction